Coupled Internationalisms: Charting Muhammad Barkatullah's Anti-colonialism and Pan-Islamism. (1st October 2019) - Siddiqui, Samee
Abstract : This article explores the transition of Muhammad Barkatullah (1864–1927), a Muslim Indian living under British colonial rule, from an intellectual demanding imperial reform to an anti-British revolutionary. Although much of the scholarly literature has analyzed Barkatullah's revolutionary activities after the First World War, the focus of this article will be on the early period of his career from the 1880s until 1914. In examining his movements, writings, and connections with various networks in the context of major global events, this article argues, first, that his revolutionary turn took place in the context of a global conversation on race, empire, and religion from the 1880s until the lead-up to the Great War, and second, that his anti-colonial (inter)nationalism was coupled with his Pan-Islamism.